Ecophysiology of the Soft Tree Fern, Dicksonia antarctica Labill - Hunt, M A; Davidson, N J; Unwin, G L; Close, D C (Austral Ecology, 2002)
Environmental constraints on gas exchange, stomatal conductance and water relations were investigated in the Soft Tree Fern, Dicksonia antarctica, at sites across its natural distribution and in the glasshouse. Dicksonia antarctica exhibited strong stomatal response down to a vapour pressure deficit (VPD) of 0.25 kPa, an unusual characteristic when compared with other ground fern species. Net photosynthetic rate may be a response of the microenvironment prevalent during frond development, reflecting acclimatory capacity. Both these ecophysiological characteristics are consistent with the ecological niche of D. antarctica, a long-lived, fire-resistant species that, during its lifetime, may be exposed to: (i) a humid environment beneath a rainforest canopy; and (ii) an exposed environment following wildfire. Maximum net photosynthesis and quantum yield of photosynthesis correlated strongly with VPD and the maximum net photosynthetic rate of 10.8 µmol m−2 s−1 was the highest yet recorded for a fern. These observations are consistent with the relatively low growth typically observed in D. antarctica on sunny, exposed sites and vice versa on cool, humid sites exposed to sunflecks. Favourable water relations maintained under conditions of moderate VPD (2.03 kPa) were probably due to stomatal control. However, inadequate rainfall or high VPD (4.98 kPa) caused water stress, recovery of which was limited by slow water transport through fronds. These observations are consistent with the limitation of D. antarctica distribution to sites sheltered from hot winds and with reliable water supply. The funnel-shaped rosette of fronds of D. antarctica may harvest rainfall and make it accessible to aerial roots situated at the base of fronds. This process may maintain favourable water relations independently of a subterranean root system. This proposed strategy of water acquisition is unique for a fern species and may eliminate a need for soil moisture competition with surrounding plant species. It is suggested that the ecophysiological characteristics observed in D. antarctica in this study may contribute to the ecological niche it occupies, which is characterized by a variable environment.